210 Clinical Utility of Gene Panel and Clinical Exome Testing in Cardiac Disease. (3rd June 2016) - Gable, Mary; Buxton, Chris; Woodward, Geoff; Wadsley, Marc; Honeychurch, Julie; Joanne, Davies; Newbury-Ecob, Ruth; Low, Karen; Donaldson, Alan; Affleck, Josphine; Whittington, Rebecca; Greenslade, Mark; et al.
Abstract : Cardiac disease is genetically heterogeneous with genes associated with multiple cardiac diseases, multiple causal genes per disease, and often multiple variants in one or more genes contributing to disease presentation. Gene panel testing, either through a specific targeted design, or by virtual analysis from the exome/clinical exome is an ideal approach for genetic diagnosis and provides information regarding complexity of these diseases. Bristol Genetics Laboratory provides a targeted gene panel for paediatric cardiomyopathy (PC) (71 genes, Agilent SureSelect) and a variety of virtual gene panels from Agilent Focussed Exome; Congenital Heart Defect (CHD) (38 genes), Aortopathy (28 genes), Arrhythmia (54 genes), Cardiomyopathy (119 genes), Connective Tissue (42 genes) Molecular Autopsy (208 genes) and bicuspid aortic valve (8 genes). Whole clinical exome analysis (6110 genes) with phenotypic prioritisation of variants based on HPO terminology using Exomiser can also be performed for patients with complex phenotypes whose phenotype does not clearly fit into a pre-defined gene panel or for patients who tested negative for a specific panel. 133 patients have been tested, including newly diagnosed cardiac cases, patients negative for other cardiac gene testing, and patients who have phenotype/genotype incompatibility where contribution of more than one gene is suspected. 41/133 (30%) patients have at least one potentially pathogenic variant. 22 patients have multiple plausible variants. We present data from the cardiac cohort tested to date and cases illustrating the utility and complexity of gene panel testing for cardiac disease including; 1) A paediatric patient with Left Ventricular Non-Compaction (LVNC), dilated aortic root and sinus brachycardia heterozygous (on the PC 71 gene panel) for a novel TMEM43 variant c.994A>G, p.(Thr332Ala) of unknown clinical significance. Further testing using a bespoke 138 gene cardiac panel from the Focused Exome detected a novel splice variant in the HCN4 gene associated with LVNC and primary sinus brachycardia (Milano et al, 2014). This patient's mother who has aortic dilation and regurgitation was heterozygous for the TMEM43 variant and the half-brother who also has dilated aortic root and LVNC did not carry either variant. 2) A large Dilated Cardiomyopathy (DCM) family with variable severity between family members, one affected cousin was heterozygous for a variant of uncertain significance in MYBPC3 c.3384G>C, p.(Glu1128Asp) and another affected cousin heterozygous for a truncating TTN variant, c.89244del, p.(Phe29748Leufs*7). Further family studies are ongoing. Detailed phenotypic assessment (using a clinical proforma) has been shown to increase diagnostic yield in patients with complex cardiac disease. Reference: Milano et al. J Am Coll Cardiol 2014;64(8):745–56